2014
DOI: 10.7771/1541-5015.1420
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of Problem-Based Learning Design Characteristics

Abstract: The increasing use of experience-centered approaches like problem-based learning (PBL) by learning and development practitioners and management educators has raised interest in how to design, implement, and evaluate PBL in that field. Of particular interest is how to evaluate the relative impact of design characteristics that exist at the individual and team levels of analysis. This study proposes and tests a multilevel model of PBL design characteristics. Participant perceptions of PBL design characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 66 publications
(93 reference statements)
1
32
0
9
Order By: Relevance
“…The central feature of PBL environments is an authentic, ill-structured problem, which is posed to groups of learners who develop a socially negotiated problem solution (Savery & Duffy, 1995). While much research surrounds the efficacy of PBL as it compares to traditional curricula, a recent study illuminates the design characteristics of PBL to successfully engage students and contribute to learning (Scott, 2014). Because this article centers on the design of a capstone course using PBL, Scott's (2014) study is of particular interest.…”
Section: Problem-based Learning and Gamesmentioning
confidence: 99%
“…The central feature of PBL environments is an authentic, ill-structured problem, which is posed to groups of learners who develop a socially negotiated problem solution (Savery & Duffy, 1995). While much research surrounds the efficacy of PBL as it compares to traditional curricula, a recent study illuminates the design characteristics of PBL to successfully engage students and contribute to learning (Scott, 2014). Because this article centers on the design of a capstone course using PBL, Scott's (2014) study is of particular interest.…”
Section: Problem-based Learning and Gamesmentioning
confidence: 99%
“…As research has shown that, compared to traditional instruction, PBL is effective in promoting long-term retention and skills, researchers have called for more attention to the study of the interaction between the learning environment and student characteristics in order to better understand how to optimize PBL environments for individual learners (Scott, 2014;Strobel & van Barneveld, 2009). The current study addresses this call by examining the role that individual motivational characteristics play in influencing engagement with and learning from the CPR model of the PBL learning environment.…”
Section: Problem-based Learning and Calibrated Peer Reviewmentioning
confidence: 99%
“…Some evidence from the medical and other professional fields shows mixed results regarding students' attitudes toward peer assessment and evaluation (Patton, 2012;van Zundert et al, 2010). Similarly, while little research has directly investigated the influence of achievement goals on engagement in PBL (Scott, 2014), theorists hypothesize that students with mastery goals are more open to collaborative learning environments, and those with performance goals approach such environments with greater caution and reserve (Senko et al, 2011). In a recent multilevel analysis examining the design effects of the PBL environment, Scott (2014) tested whether AGO predicts several outcomes in a PBL environment, including self-directed learning (SDL) and perceptions of the learning environment.…”
Section: Achievement Goal Orientation and Peer Assessment Systemsmentioning
confidence: 99%
See 2 more Smart Citations